PENGARUH METODE PROBLEM SOLVING DAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PRESTASI BELAJAR IPS DI SEKOLAH DASAR ISLAM TERPADU - Asep - Kurniawan (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2019)
The purpose of the research was to reveal the extent of the effect of problem solving methods and cooperative types of think pair share on social science learning achievements in Islamic elementary full day school Sabilul Huda Cirebon. The research was quantitative research with an associative approach. The population in this study was 350 students of class VI. The sampling technique was cluster sampling, i.e. 77 students. The results of his research were (1) problem solving learning methods in social studies get a tendency of 66% or 51 respondents who used problem solving learning methods with very good categories. Think Pair Share Cooperative learning of social studies, respondents got a tendency of 61% or 47 respondents used cooperative learning of Think Pair Share had a very good category. (2) There was a significant influence of the problem solving learning method on social studies learning achievement in Islamic elementary full day school Sabilul Huda. (3) Cooperative learning of Think Pair Share had a greater influence than the problem solving learning method on social studies learning achievement in Islamic elementary full day school Sabilul Huda.